2022
DOI: 10.1161/strokeaha.120.033025
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Lesion Water Uptake as Stroke Imaging Biomarker: A Tool for Treatment Selection in the Extended Time Window?

Abstract: Background and Purpose: Patients presenting in the extended time window may benefit from mechanical thrombectomy. However, selection for mechanical thrombectomy in this patient group has only been performed using specialized image processing platforms, which are not widely available. We hypothesized that quantitative lesion water uptake calculated in acute stroke computed tomography (CT) may serve as imaging biomarker to estimate ischemic lesion progression and predict clinical outcome in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In another study, postthrombectomy NWU has been compared with baseline NWU measurements on admission CT and a reduction in NWU interpreted as an improvement or reversal of edema. 14,26,27 Our data on the influence of iodine and hemorrhagic transformation also challenges such interpretation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In another study, postthrombectomy NWU has been compared with baseline NWU measurements on admission CT and a reduction in NWU interpreted as an improvement or reversal of edema. 14,26,27 Our data on the influence of iodine and hemorrhagic transformation also challenges such interpretation.…”
Section: Discussionmentioning
confidence: 81%
“…However, exclusion of hemorrhagic transformation on follow-up imaging at a patient or voxel-level has not been consistently applied across studies using NWU. For example, patients with hemorrhagic transformation were excluded from analysis in the initial papers describing the methodology of NWU 17,25 and some subsequent studies 16,26,27 but were included in other analyses. 14,15 However, we demonstrated for the first time that thrombectomy also diminished the accuracy of NWU even when visible hemorrhagic transformation was excluded, possibly due to retained iodine contrast that was visually inconspicuous.…”
Section: Discussionmentioning
confidence: 99%
“…While this hypothesis is worth further investigation, the fact that the model, as it is, explains the same amount of variability for early and late favorable outcome argue for a potential role of other acute cerebral compensatory mechanisms/failures that escape the conventional work-up. Indeed, several parameters not assessed by automated softwares like Rapid , such as venous outflow assessment from acute stroke angio-CT ( 39 ) or the quantitative lesion water uptake calculated from non-contrast head CT ( 40 ), have been shown to be associated with favorable outcomes. Similarly, treatment related parameters beyond TTR can provide prognostic information such as the luxury perfusion reflected by early venous filling after EVT that predicts early favorable outcome ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NWU began immediately after AIS with the extravasation of fluid into ischemic tissue through the BBB, which may allow the detection of ionic edema earlier and more sensitively than previous methods (17). Previous studies reported that NWU within the ischemic core was an independent predictor for patients with AIS developing malignant edema (9,18,19) and poor neurological outcomes (8,10). The cerebral ischemic lesion consists of a central irreversible necrotic zone and reversible peripheral ischemic penumbra.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative net water uptake (NWU) is a relatively novel neuroimaging marker of early brain edema after AIS, first described in 2016 based on admission multimodal CT (7). Researchers subsequently reported that NWU within the ischemic core can identify patients within the thrombolysis time window and predict poor outcomes at 90 days, and those with malignant edema (8)(9)(10). In the hyperacute stage of AIS, cytotoxic edema will lead to endothelial cell swelling, further blood-brain barrier (BBB) breakdown, increased permeability, and ultimately may contribute to hemorrhagic transformation (HT).…”
Section: Introductionmentioning
confidence: 99%